Gender and GMOs: Understanding Floridians attitudes toward GMOs through the lens of Social Judgment Theory - Joy N Rumble; Lisa K Lundy; Brittany Martin; Sandra Anderson (Journal of Applied Communications, 2017)
Social judgement theory was utilized to determine if men and women showed different acceptance of messages about genetically modified (GM) foods. The primary objective was to determine if females and males had a different latitude of acceptance toward statements about GM foods. Researchers found significant differences between males and females with more males accepting messages about GM foods than females. Additionally, there were several statements with wide latitudes of acceptance across genders. These statements represent a common ground and are a good starting point for conversations about GM food.
Keywords: Genetically modified foods; genetic modification technology; social judgement theory; consumer perceptions; consumer attitudes; gender